Algae Biomass cultivation in fish farm effluent for biodiesel production - Enwereuzoh, Uzochukwu Onyinyechukwu (My University, 2021)
Microalgae research is driven by the need for alternative fuels for reasons such as climate change mitigation, depleting fossil fuel reserves, increased energy demand and economic growth. Some setbacks of producing commercial microalgae biodiesel include purchasing nutrients, the supply of large volumes of water, low biomass productivity, low lipid accumulation and desirable fatty acid composition. However, the increased cost of microalgae cultivation is influenced by the high cost of inorganic nutrients and large volumes of water required for propagation. On the other hand, the use of fertiliser for the production of microalgae may be counterproductive, as the production of fertiliser through conventional technologies release carbon dioxide. These purchased synthetic nutrients can be replaced by nutrients in different agricultural wastes, for example. One type of suitable agricultural waste with suitable nutrient concentration for cultivating microalgae biomass is the aquaculture wastewater. Different studies have shown that nutrients required for microalgae cultivation such as ammonia, nitrate and phosphates are in a suitable range in aquaculture wastewater. These nutrients have supported the cultivation of microalgae in aquaculture wastewater for different purposes. Previous studies in microalgae wastewater treatment have focused on cultivating microalgae in other sources of wastewater, with little studies on using aquaculture wastewater. The few studies using fish farm wastewater (FFW) have focused on growing microalgae for biomass production and nutrient removal with minimal research on the composition of the biomass obtained, biodiesel production and properties of biodiesel obtained, the economic and environmental implication of using FFW nutrients instead of purchased nutrients. The gap in using FFW for microalgae biodiesel production is the reason this research is aimed at reducing the cost of microalgae biomass cultivation for biodiesel production, by recycling nitrogen and phosphorus in nutrient-rich fish farm effluent which is released in a form that is preferred by microalgae (that is NH3 for nitrogen and PO4-3 for phosphate) for microalgae growth. Therefore, instead of purchasing fertilizer, those nutrients from farm effluent were exploited in the cultivation of microalgae for biodiesel production. As a result, this supplied nutrients and large volumes of water required for microalgae cultivation treated the FFW by removing these nutrients and mitigate the environmental challenges of discharging nutrient-rich effluents. Three high lipid accumulating algae species, according to other studies, were used in this research work (Tetradesmus obliquus, Heterochlorella luteoviridis and Chlamydomonas reinhardtii). Each species was cultivated in a Tris-acetate phosphate (TAP) standard growth media and fish farm effluent at the same conditions. The specific growth rate, biomass yield, biomass productivity, lipid content, lipid productivity, carbohydrate content, carbohydrate productivity, protein content ,protein productivity, rate of CO2 uptake and carbon content were determined. The biodiesel was produced from microalgae species that were cultivated in the standard growth medium in addition to modified and unmodified fish effluent. The same species were also grown in modified (low nutrient) fish farm effluent to compare fuel properties and level of accumulation of protein and carbohydrate with those obtained in unmodified fish farm effluent. The fatty acid methyl ester composition of the biodiesel aided in determining the properties of the produced biodiesel (cetane number, iodine value, cold filter plugging point, kinematic viscosity, density and degree of saturation). A theoretical cost estimation and a life cycle assessment was used to determine the environmental benefits of using fish farm effluent nutrients for the cultivation of microalgae feedstock for biodiesel production. Higher growth, biomass yield, lipid content and lipid productivity was obtained in microalgae species cultivated in FFW. Microalgae grown in FFW had better uptake of CO2 than the same species cultivated in the standard growth media. Comparable fuel property was obtained across different growth media. Fuel properties had characteristics within specifications of both ASTM D6751-02 and EN 14214 standards. Chlamydomonas reinhardtii in all culture media had better CFPP property and is more suited for cold climates with freezing temperatures. FFW growth media had a lesser environmental and cost impact which came mostly from electricity used for supply of light and CO2gas supply
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Science in Engineering, 2021